2014
DOI: 10.1038/nchem.2006
|View full text |Cite
|
Sign up to set email alerts
|

Control of ultrafast molecular photodissociation by laser-field-induced potentials

Abstract: Experiments aimed at understanding ultrafast molecular processes are now routine, and the notion that external laser fields can constitute an additional reagent is also well established. The possibility of externally controlling a reaction with radiation increases immensely when its intensity is sufficiently high to distort the potential energy surfaces at which chemists conceptualize reactions take place. Here we explore the transition from the weak- to the strong-field regimes of laser control for the dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
170
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(176 citation statements)
references
References 39 publications
5
170
0
1
Order By: Relevance
“…These interactions lead to emergent and controllable behavior in assembly phenomena, [27][28][29][30] organic synthesis, 31 protein folding, 32 the detection of DNA, 33 and photodissociation. 34 Knowledge of the mechanism by which these interactions mediate reactive flow provides a methodological tool in the design of molecular devices with unique functionality. [35][36][37] Materials that undergo conformational changes in response to an external trigger offer examples of such emergent technology.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions lead to emergent and controllable behavior in assembly phenomena, [27][28][29][30] organic synthesis, 31 protein folding, 32 the detection of DNA, 33 and photodissociation. 34 Knowledge of the mechanism by which these interactions mediate reactive flow provides a methodological tool in the design of molecular devices with unique functionality. [35][36][37] Materials that undergo conformational changes in response to an external trigger offer examples of such emergent technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experiments have shown that it is possible to achieve unprecedented control over photodissociation reactions. [8][9][10] . The LIPs provide a new playground where essentially new electronic states are created and these new chemical species are an open door to control the chemistry of simple molecules or to increase our understanding of the molecular dynamics in excited states.…”
Section: Discussionmentioning
confidence: 99%
“…Then the energy differences between V a e ðRÞ and the molecular potentials V 1 ðRÞ and V 2 ðRÞ at the time of the sudden switch off of S ðtÞ will be imprinted in the final KEDs. [10] …”
Section: Control Of the Kinetic Energy Distributionmentioning
confidence: 99%
See 2 more Smart Citations